AB1015 CENTRAL NERVOUS SYSTEM VASCULITIS PRECEDING. (June 2019) - Henoch-Schönlein Purpura, A; ,; Simonini, Gabriele; Fusco, Eleonora; Maccora, Ilaria; Rosati, Anna; Cimaz, Rolando; Giani, Teresa
Abstract : Background: Henoch-Schönlein purpura (HSP) is a systemic small vessel vasculitis and represent the most common cause of non-thrombocytopenic purpura in children; vasculitis very rarely can involve internal organs. Central nervous system (CNS) is exceptional. Objectives: We report the case of a patient with CNS vasculitis who presented HSP 4 months after the stroke and during corticosteroid withdrawal. Methods: Case report Results: A 9-year-old Caucasian boy was admitted to our hospital due to sudden onset of severe headache and left faciobrachial hemiparesis associated with facial palsy and dysarthria. Brain MRI revealed hyperintense signal changes in amygdala, putamen, and internal capsule, suggestive of recent cerebral ischemic lesion. Magnetic resonance angiography showed asymmetry of internal carotid arteries and middle cerebral artery stenosis, suggestive for a vasculitic-inflammatory nature. He received high dose intravenous methylprednisolone, followed by oral corticosteroids with nearly complete recovery. He was discharged on oral prednisone and low-dose aspirin. In the following months a slow tapering of prednisone was attempted. Four months after the stroke, while receiving prednisolone 0.5 mg/kg/day, he presented with sudden onset of purpuric rash on extensor surfaces of the lower extremities, buttocks and arthralgia of the upper and lower extremities. Painful scrotal swelling and abdominal pain were also present. Serial urinalyses were normal. The patient underwent a second MRI of the brain, which ruled out new-onset inflammatory lesions. Therefore, he received intravenous high dose steroids, with complete remission. Sequencing of adenosine deaminase 2 (ADA2) gene ruled out ADA2 deficiency. Conclusion: We report a case of CNS vasculitis preceding HSP by several months; intriguingly, HSP developed while the patient was under corticosteroid treatment. The exact nature of the association needs to be clarified, to determine if the association was determined by a common pathogenic mechanism or by chance. References: [1] AkÇaboy M, Fidan K, Kandur Y, et al. Cerebral Vasculitis in Henoch-Schönlein Purpura: A Case Report. Arch Rheumatol. 2017. Mar 24;32(3):264-267. [2] Bérubé MD, Blais N, Lanthier S. Neurologic manifestations of Henoch-Schönlein purpura. Handb Clin Neurol. 2014;120:1101-11. [3] Suh JS, Hahn WH, Cho BS, Kim SD, Hong IK. A rare case of cerebral vasculitis in Henoch-Schönlein purpura with emphasis on the diagnostic value of magnetic resonance angiography (MRA) and single-photon emission computed tomography (SPECT) given normal magnetic resonance imaging (MRI). Int J Dermatol. 2010 Jul;49(7):803-5. Acknowledgement: Federica Barbati, MD; Sara Abu-Rumeileh, MD Disclosure of Interests: edoardo marrani: None declared, Gabriele Simonini Grant/research support from: Abbvie, Speakers bureau: Abbvie, Eleonora Fusco: None declared, Ilaria Maccora: None declared, Anna Rosati: None declared, Rolando Cimaz: None declared, Teresa Giani: None declared